An Intra-Industry Comparison of Alternative Income Concepts and Relative Performance Evaluations. - Kratchman, Stanley H.; Malcom, Robert E.; Twark, Richard D. (The Accounting Review, 1974)
Abstract This article presents an intra-industry comparison of alternative income concepts and relative performance evaluations. While the amount of research on basic income concepts continues to be voluminous, questions of practical impact only recently have begun to receive much attention. In order to contain the research to a manageable size, a single industry, real estate investment trust (REIT), was selected for investigation. Also, only one of the three basic forms of real estate investment trusts, the equity real estate investment trust, was selected. There are several reasons for choosing this particular industry and type of trust. REITs are a homogeneous grouping of companies with a relatively limited history. Thus, for these companies it was expected that financial data would be available from the first year of operations to the current period. Such data are desirable in order to adjust properly for price-level changes. Since REITs are a homogeneous group, the application and selection of specific price-level adjustments are not as difficult as with less homogeneous companies.